Beyond this moment - Alexander, Tamera (Alexander, Tamera. Timber Ridge reflections., 2009)
Sheriff James McPherson was eager to hire a schoolteacher, but Dr. Molly Whitcomb isn't what he expected. His instincts about people--which rarely miss the mark--tell him she's hiding something. And when Molly's secret is revealed, her reinvented life begins to unravel. What's more, she risks losing her newfound relationship with the sheriff and her renewed faith in God.